2007
DOI: 10.1371/journal.pmed.0040090
|View full text |Cite
|
Sign up to set email alerts
|

Exquisite Sensitivity of TP53 Mutant and Basal Breast Cancers to a Dose-Dense Epirubicin−Cyclophosphamide Regimen

Abstract: BackgroundIn breast cancers, only a minority of patients fully benefit from the different chemotherapy regimens currently in use. Identification of markers that could predict the response to a particular regimen would thus be critically important for patient care. In cell lines or animal models, tumor protein p53 (TP53) plays a critical role in modulating the response to genotoxic drugs. TP53 is activated in response to DNA damage and triggers either apoptosis or cell-cycle arrest, which have opposite effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
133
1
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(156 citation statements)
references
References 44 publications
19
133
1
3
Order By: Relevance
“…In the clinics, the question has not yet received definitive answers; it appears, however, that a loss of p53 function is frequently associated with resistance to treatment in several malignancies . However, in a recent study on basal-like breast cancers treated by neo-adjuvant chemotherapy using an alkylating agent (cyclophosphamide), all tumours harbouring a mutated p53 presented a complete pathological response to treatment (Bertheau et al, 2007).…”
mentioning
confidence: 97%
“…In the clinics, the question has not yet received definitive answers; it appears, however, that a loss of p53 function is frequently associated with resistance to treatment in several malignancies . However, in a recent study on basal-like breast cancers treated by neo-adjuvant chemotherapy using an alkylating agent (cyclophosphamide), all tumours harbouring a mutated p53 presented a complete pathological response to treatment (Bertheau et al, 2007).…”
mentioning
confidence: 97%
“…In previous studies (Bertheau et al, 2002(Bertheau et al, , 2007, we have shown in non-inflammatory locally advanced breast cancers that TP53 mutations are highly predictive of complete pathological response to high-dose epirubicin/cyclophosphamide chemotherapy. TP53 is known to control genomic integrity (Vogelstein et al, 2000), and is induced by cytotoxic drugs (Lowe et al, 1993;Bunz et al, 1999), whereas its potential role as a prognostic and a predictive marker in cancer patients remains controversial (Vousden and Prives, 2005;Berns, 2006).…”
mentioning
confidence: 85%
“…Whereas obviously, we cannot explore the genome of tumours that underwent complete response, those that were not eradicated can be analysed. Note that we have previously shown that TP53 mutant tumours that did not undergo complete remissions have a worse prognosis than the other groups (Bertheau et al, 2007). This might be caused by chemotherapy-induced additional genetic changes that favour progression.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Owing to the differing drug regimens and tumour subtypes tested, the analysis of TP53 mutations (and p53 protein expression) and anthracycline response has given conflicting results (Bidard et al, 2008). Although some reports suggest that TP53 mutations confer resistance to anthracyclines (Aas et al, 1996;Rahko et al, 2003), others have shown mutations to increase sensitivity (Bertheau et al, 2002(Bertheau et al, , 2009. Similarly, BRCA1 has multiple roles in breast cancer including DNA damage repair, transcriptional regulation, and regulation of cell cycle checkpoints.…”
Section: Other Potential or Emerging Markersmentioning
confidence: 99%